2014
DOI: 10.1371/journal.pone.0090859
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA Is Expressed across the Eukaryotic Tree of Life

Abstract: An unexpectedly large fraction of genes in metazoans (human, mouse, zebrafish, worm, fruit fly) express high levels of circularized RNAs containing canonical exons. Here we report that circular RNA isoforms are found in diverse species whose most recent common ancestor existed more than one billion years ago: fungi (Schizosaccharomyces pombe and Saccharomyces cerevisiae), a plant (Arabidopsis thaliana), and protists (Plasmodium falciparum and Dictyostelium discoideum). For all species studied to date, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
535
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(546 citation statements)
references
References 40 publications
7
535
0
4
Order By: Relevance
“…87 It has additionally been proposed that many Drosophila circular RNAs are generated independently of repeats. 29 This suggests the existence of alternative mechanisms for circular RNA biogenesis.…”
Section: Circular Rnas Generated Via Exon Skippingmentioning
confidence: 99%
“…87 It has additionally been proposed that many Drosophila circular RNAs are generated independently of repeats. 29 This suggests the existence of alternative mechanisms for circular RNA biogenesis.…”
Section: Circular Rnas Generated Via Exon Skippingmentioning
confidence: 99%
“…49 In addition, various noncoding RNAs in archaea are processed to yield circular RNAs through poorly understood mechanisms. 50 In summary, thousands of protein-coding genes generate circular RNAs 13,[28][29][30][31][32] and we are beginning to understand the key elements that facilitate their biogenesis. Both computational analyses and plasmid-based experiments have pointed to a key role for base pairing between intronic complementary sequences in promoting most backsplicing events.…”
Section: 304142mentioning
confidence: 99%
“…Due to their closed loop form, they cannot be mapped directly to the genome, which is probably one of the reasons for the late discovery of these relatively new RNA species. They appear to be ancient, conserved regulators of eukaryotic gene expression [9] and were initially detected in ribosomal depleted RNA-seq data [2]. Due to the lack of free ends circRNAs are resistant to exonucleases and have reduced rates of turnover [10].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for expression of circRNA was found in Drosophila [6] [12] where over 2500 circRNAs were annotated [14]. Several studies showed that different circRNA structures can be produced by alternative splicing from the same gene [9] [12], and this feature adds considerably to their diversity.…”
Section: Introductionmentioning
confidence: 99%